The Use of Reflection as an Effective Leadership Practice: An Introduction: AEC811/WC473, 9/2024 - Chiarelli, Christy (EDIS, 2024)
The purpose of this publication is to emphasize the practice and importance of reflection for leaders. By highlighting reflective leadership, this publication aims to provide additional resources for leaders navigating their daily leadership responsibilities. This reflective leadership series discusses the importance of reflection, the benefits and barriers to employing reflective leadership, models of reflective leadership, and finally, suggested practices for implementing reflection into one’s leadership practice.